Metals in superficial sediments of a cascade multisystem reservoir: contamination and potential ecological risk - Cardoso-Silva, S. [UNESP]; Meirelles, S. T.; Frascareli, D. [UNESP]; López-Doval, J. C.; Rosa, A. H. [UNESP]; Moschini-Carlos, V. [UNESP]; Pompêo, M. (Springer Nature, 2017)
Cascade multisystem reservoirs are extremely complex ecosystems that require studies to improve understanding of their dynamics and functioning, including the effects of contamination with metals. In this work, superficial sediments were collected during two sampling campaigns (in the dry and rainy seasons) at 19 sites along a cascade multisystem reservoir in São Paulo, Brazil, formed by five reservoirs. The sediments were evaluated considering the following parameters: pseudo-total metals (Cu, Cd, Cr, Ni, Pb, Zn, Mn, Fe, and Al); bioavailable metal (Cu); organic matter; total phosphorus; total nitrogen; and grain size. In the last reservoir of this system, the enrichment factors indicated enrichment of Cu, Pb, Zn, and Mn. Despite this increased metals content, the pollution load index indicated an absence of pollution (PLI < 1), and the ecological risk was low (RI < 150). According to sediment quality guideline criteria, toxicity was unlikely to occur. Principal component analysis (PCA) and one-way ANOVA indicated heterogeneity among the reservoirs (P < 0.01) and between the sampling periods. The PCA results confirmed higher levels of nutrients in the upstream reservoirs, suggesting that nutrients were precipitated in the first reservoirs of the system. On the other hand, metal levels were higher in the downstream reservoirs. The main source of metal contamination in the region was the use of copper sulfate as an algicide. This included contamination by Pb and Zn, due to impurities in the copper sulfate employed. High Mn levels were associated with wastewater discharges and erosion. In addition to helping to improve understanding of the dynamics of metals in cascade multisystem reservoirs, this work could serve as a useful tool for the management of reservoirs with contaminated sediments.
Keywords: Cascade reservoir; Copper; Metal; Sediments